Integrated Reporting Sebagai Upaya Mendorong Industri Kelapa Sawit yang Berkelanjutan - Riantri Barus; Diana Chalil (Universitas Medan Area, 2023)
According to Law No. 40 of 2007, companies in Indonesia must only make annual reports containing directors' reports, management reports, analysis and discussion reports, or operational and financial performance reports. However, this information is still insufficient to meet report users’ needs in making a decision. In 2011, the International Integrated Reporting Council (IIRC) issued an Integrated Reporting reporting system that provides complete information on company activities, including activities related to social, environmental, and financial aspects. Through this reporting system, companies can provide complete and reliable information to all stakeholders, including investors, and restore investor confidence. In Indonesia, this reporting system is still voluntary and has not become an obligation. This reporting system will be very relevant to plantation companies, especially oil palm, given the many negative issues about unsustainable oil palm plantation entrepreneurs causing investors to lose confidence in investing in companies in the plantation sector, resulting in a decline in the share price of the plantation sector. This research was conducted on plantation companies listed on the Indonesia Stock Exchange, using data from all company reports from 2014 to 2020. The analytical method used is content analysis, average difference test, and simple regression analysis. The results show that no companies have implemented integrated reporting; companies are still limited to issuing annual reports. However, several companies have issued sustainability reports. The information disclosed is also limited to general matters rather than detailed information, as per the GRI standards. This is because oil palm plantations do not produce finished products sold directly to consumers, causing many aspects to not meet the standards.